2008
DOI: 10.1002/j.0022-0337.2008.72.3.tb04498.x
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Influence of Admissions Criteria and Cultural Norms on Success in an International Dental Studies Program

Abstract: This study determines the extent to which admissions criteria and cultural norms predict the success of a foreign-trained dentist in a United States dental educational program. Correlation and regression tests were applied to an eleven-year period from 1994 to 2004 of retrospective admissions data for 144 International Dental Studies Program students. Five cultural norms were derived from the collective cultural dimensions of a scholarly work of validated multinational surveys by Geert Hofstede. These five cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…In a study conducted in Sri Lanka in 1999 involving 460 first‐year dental students, English knowledge was the only factor that significantly predicted their academic performances explaining almost 60% of its variance . A lack of language proficiency may well hinder communication with patients, fellow students and teachers as well as adversely affecting performance in learning and assessments, finally reflecting in their examination scores, GPA or grades .…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Sri Lanka in 1999 involving 460 first‐year dental students, English knowledge was the only factor that significantly predicted their academic performances explaining almost 60% of its variance . A lack of language proficiency may well hinder communication with patients, fellow students and teachers as well as adversely affecting performance in learning and assessments, finally reflecting in their examination scores, GPA or grades .…”
Section: Introductionmentioning
confidence: 99%
“…After title and abstract screening, 29 publications that did not answer the focused question or were duplicates were excluded. In total 18 articles were sought, including nine articles [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] discussing workforce diversity in dentistry ( Table 1 ); and nine articles [ 1 , 2 , 8 , 9 , 10 , 22 , 23 , 24 , 25 ] discussing licensing process for foreign-trained dentists ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies from medical journals also noted a similar pattern: that IMGs were more likely to have higher degrees than were USMGs 17 . Considering the competitiveness of entering US residency programs, only top foreign students could be selected; however, due to extreme variations in educational and grading systems worldwide, academic ranks may not represent an objective indicator to determine students’ performance in their previous training 4,11 . Although having a higher degree might indicate an academic engagement and could be considered favorable by program directors, similar to research and scholarly activities, attainment of an advanced degree does not predict the resident's performance or future career in academics 19 …”
Section: Discussionmentioning
confidence: 99%
“…This also explains why FTDs have more clinical experience than USTDs. It had been suggested that these experiences might benefit US training programs by adding diversity, maturity, and different perspectives on healthcare; 3,8 however, one study showed that having dental licenses from foreign countries did not predict students’ success in US dental programs 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation